2016
DOI: 10.4238/gmr.15017266
|View full text |Cite
|
Sign up to set email alerts
|

Y-STR genetic screening by high-resolution melting analysis

Abstract: ABSTRACT. Currently, the widely used automated capillary electrophoresis-based short tandem repeat (STR) genotyping method for genetic screening in forensic practice is laborious, time-consuming, expensive, and technically challenging in some cases. Thus, new molecular-based strategies for conclusively identifying forensically relevant biological evidence are required. Here, we used high-resolution melting analysis (HRM) for Y-chromosome STR genotyping for forensic genetic screening. The reproducibility of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…HRM analysis is a one-tube and post-PCR method based on the intercalation of fluorescence dye into double-strand DNA. Fluorescence changes during dsDNA melting enable to discriminate genotypes [ 22 ]. High-resolution melting analysis is a relatively easy and rapid (the entire procedure can be completed in 1.5–2 hours), one-step, cost-effective application [ 22 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…HRM analysis is a one-tube and post-PCR method based on the intercalation of fluorescence dye into double-strand DNA. Fluorescence changes during dsDNA melting enable to discriminate genotypes [ 22 ]. High-resolution melting analysis is a relatively easy and rapid (the entire procedure can be completed in 1.5–2 hours), one-step, cost-effective application [ 22 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence changes during dsDNA melting enable to discriminate genotypes [ 22 ]. High-resolution melting analysis is a relatively easy and rapid (the entire procedure can be completed in 1.5–2 hours), one-step, cost-effective application [ 22 , 41 , 42 ]. Moreover, it was found that STRs analysed by HRM had more genotypes than in capillary electrophoresis [ 22 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations